Two‐step biological approach for treatment of rapeseed meal. Issue 2 (20th January 2020) - Tie, Yu; Li, Li; Liu, Jun; Liu, Chaolan; Fu, Junjie; Xiao, Xiongjun; Wang, Guoqiang; Wang, Jingfeng
Abstract : Abstract: Rapeseed meal (RSM) is an important source of protein, but its value is limited due to the poor digestibility and the presence of many antinutritional factors. In this study, a two‐step biological method was developed for detoxifying RSM and increasing its protein value. In the first stage, various detoxifying enzymes and proteases were produced by Aspergillus niger during solid‐state fermentation (SSF). In the second stage, coordinated enzymatic hydrolysis was employed to further degrade the antinutritional factors and macromolecular proteins in the fermented RSM. Following fermentation at 30 °C for 48 hr and enzymatic hydrolysis at 45 °C for 24 hr, the content of trichloroacetic acid soluble protein (TCA‐SP) and glucosinolates (GLS) in RSM was increased by 81.70% and reduced by 30.06%, respectively, compared with that obtained using the SSF process alone. Moreover, to improve the efficiency of enzymatic hydrolysis, the yield of acid protease was increased by optimizing the composition of the medium so that the TCA‐SP content was increased to 208.39 mg/g and accounted for 51.62% of the total RSM protein, which was 99.36% and 629.66% higher than that in the fermented RSM and control, respectively. Overall, these results demonstrate that the two‐step process could be more effective for the degradation of the antinutritional factors and improvement of the protein quality of RSM compared to use of the SSF method alone, which may improve the utilization of RSM in food and animal feed. Practical Application: Rapeseed meal (RSM) is a protein source that provides high‐quality nutrition and can be applied to the development of value‐added products for humans and animal feed. To improve the utilization of RSM, a combined method of solid‐state fermentation and enzymatic digestion was developed. Compared with the traditional solid‐state fermentation method, the present method further improves the quality of RSM and demonstrates improved efficacy in increasing the small peptide content while reducing the levels of antinutritional factors.